A Pilot Study on the Efficacy of a Single Intra-Articular Administration of Triamcinolone Acetonide, Hyaluronan, and a Combination of Both for Clinical Management of Osteoarthritis in Police Working Dogs - Alves, João C.; Santos, Ana; Jorge, Patrícia; Lavrador, Catarina; Carreira, L. Miguel (Frontiers in Veterinary Science, 2020)
Objectives: To describe and compare the use and effectiveness of a single intra-articular injection (IA) of triamcinolone acetonide (TA), hyaluronan (HA) and a combination of both (TA+HA) in police working dogs with natural occurring hip osteoarthritis (OA). Study design: Prospective, randomized, single-blinded study. Sample population: Thirty animals with naturally occurring hip OA. Methods: Animals were randomly divided in three groups: GT, treated with 20mg of TA; GH, treated with treated 20mg of HA; and GTH, treated with a combination of 20mg of TA and 20mg of HA per hip joint. Response to treatment, measured by the Canine Brief Pain Inventory (divided in Pain Interference Score – PIS and Pain Severity Score - PSS) and the Hudson Visual Analogue Scale (HVAS), was evaluated in seven different time points: T0 (before treatment), T1 (after 15 days), T2, T3, T4, T5 and T6 (after 1, 2, 3, 4 and 5 months respectively).Results were compared using a Kruskal-Wallis test or a Wilcoxon signed ranks test, and p<0.05 was set. Results: Comparing results of different time points with T0, significant differences were registered in GH at T1 for HVAS (p=0.03) and PIS (p=0.04); and in GTH at T1 (p=0.05 for HVAS and p<0.05 for PIS), T2 (p<0.04 for PIS), T3 (p<0.03 for HVAS and p=0.05 for PIS), T4 (p<0.03 for HVAS and p<0.05) and T5 (p<0.05 for HVAS). No significant differences were found between groups when comparing scores in each time point. Individual treatment is considered successful with a reduction of ≥1 for PSS or ≥2 for PIS. In GTH, treatment was successful in four animals between T1-T5 (40%, n=10) and three at T6-T7 (30%, n=10) for PSS and three animals of GTH at T1 (30%), two at T2 (20%), three between T3-T4 (30%) and two between T5-T7 (20%). Conclusions and Clinical Relevance: This study provides direct information on treatment modalities in patients with hip OA. Intra-articular injection with TA and HA may be a option for dogs with OA, particularly in combination, as they provide significant improvements of PIS and HVAS scores. Individual PIS, PSS and HVAS scores improved in some animals .